Empowering Smallholder Goat Farmers through Participatory Extension: Enhancing Knowledge and Management of Ruminal Tympany in Rural Indonesia - Wigati, Sri; Decline, Vega; Viastika, Yanita Mutiaraning; Safitri, Jessica Anggun; Rizky, Asri; Syarifuddin, Ahmad; Damhuri, Dedi; Shaddiq Rosa, Teuku (Jurnal Karya Abdi Masyarakat, 2025)
Ruminal tympany is a major digestive disorder that limits productivity and increases mortality in smallholder goat production systems, particularly in rural areas with limited veterinary support. This community service study aimed to improve farmers’ knowledge and awareness of ruminal tympany through a participatory extension approach. The program applied a one-group pretest–posttest quasi-experimental design involving 30 smallholder goat farmers in Panerokan Village, Jambi Province, Indonesia. The intervention combined lectures, interactive group discussions, and hands-on demonstrations focusing on disease identification, risk factors, preventive feeding management, and basic on-farm response strategies. Farmers’ knowledge was measured using structured questionnaires administered before and after the intervention. The results showed a substantial increase in knowledge, with mean scores improving from 45% in the pretest to 77% in the posttest across all assessed indicators. The novelty of this program lies in its practice-based and context-specific extension model that integrates scientific knowledge with local feeding practices. The findings suggest that participatory extension interventions can effectively strengthen farmers’ capacity for early detection and prevention of ruminal tympany, thereby contributing to more sustainable and resilient smallholder goat farming systems when supported by continued mentoring and follow-up initiatives.